INHERITANCE RIGHTS FOR ADULTERY CHILDREN; AN ANALYSIS OF PROSERITY APPROACH TO THE INHERITANCE RIGHTS FOR ADULTERY CHILDREN IN THE ISLAMIC LAW COMPILATION - Ikbal Hanafi Hasibuan; Saidurrahman Saidurrahman; Azhari Akmal Tarigan (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This research presents the latest information about the inheritance rights of adultery children, analysis of the prosperity approach to the inheritance of adultery children in the Compilation of Islamic Law. The research is presented in a qualitative form with normative legal research type, which aims to investigate the norms of Islamic law to find the rules of behavior that are considered the best and can be applied to provide legal provisions for a case. This research uses a philosophical approach, namely the study of the basic values of Islamic law in answering a legal problem. Furthermore, research makes prosperity theory as an analytical tool in analyzing data. In the end, this research concluded, adultery with biological father has a civil relationship, both in terms of lineage and inheritance. Ownership of lineage relations based on the opinion of Ibn Qayyim al-Jauziyyah, MUI Fatwa, Decision of the Constitutional Court Number 46 / PUU-VIII / 2010. Regarding inheritance, researchers disagree with the Indonesian Ulama’ Council and the Constitutional Court's Decision Number 46 / PUU-VIII / 2010. Researchers believe that the portion received by adultery from their biological fathers is equated with the legal position of inherited children. Researchers see, if the adultery child is given the compulsory testament it becomes something that is ambiguous with the status of the right of adultery with the biological father. One side of the Constitutional Court Ruling Number 46 / PUU-VIII / 2010 confirmed that the adultery child is a child and has a relationship with his biological father, but on the other hand in the case of inheritance is not treated as a child of his biological father. Giving a compulsory will as a scapegoat by the Constitutional Court (government) to adultery children or on family law issues to provide solutions to all marital problems and consequences that do not follow administrative procedures in Indonesia and granting inheritance of inheritance rights is a sanction for adulterers using the theory upside down in Indonesia. Keywords: Adultery Children, Inheritance Islamic Law Compilation, Prosperity